Catatonia in ICD-11 - Jonathan P. Rogers; Jo Ellen Wilson; Mark A. Oldham (BMC Psychiatry)
Abstract In the International Statistical Classification of Diseases and Related Health Problems Version 11 (ICD-11), the diagnostic criteria for catatonia have been extensively revised. We provide context for these changes beginning with a brief history of how catatonia has been conceptualized and a description of how the criteria for catatonia have changed across ICD versions. We also compare ICD-11 with the criteria in the latest Diagnostic and Statistical Manual of Mental Disorders (i.e., DSM-5-TR), consider clinical implications of the changes in ICD-11, and highlight conceptual areas in need of further development. Described in 1874 by Karl Kahlbaum, catatonia was subsequently subsumed into the Kraepelinian concept of dementia praecox. This was reflected in versions of ICD up to ICD-9, which considered catatonia exclusively as a form of schizophrenia. ICD-10 introduced the diagnosis of organic catatonic disorder but did not incorporate the growing evidence that catatonia can occur in psychiatric conditions such as mood and autism-spectrum disorders. ICD-11 conceptualizes catatonia as an independent disorder with a common clinical phenotype regardless of associated condition, if present. In ICD-11, catatonia diagnosis requires at least three clinical features from the following categories: decreased, increased or abnormal psychomotor activity. These features may come from any combination of the categories, but only one from the increased psychomotor activity category should be counted. The four catatonia diagnoses in ICD-11 are catatonia associated with another mental disorder, catatonia induced by substances or medications, secondary catatonia syndrome and catatonia, unspecified. This expanded view of catatonia more closely resembles DSM-5-TR, which also recognizes catatonia associated with several psychiatric and general medical conditions. ICD-11 also offers guidance on distinguishing catatonia from similar behavioural features of other conditions, such as psychomotor retardation in depression, delirium, and factitious disorder. This new classification stands to improve recognition of catatonia and our hope is that it may lead to a growing awareness of the wide range of conditions associated with it. Ultimately, a better understanding of catatonia should contribute to improved outcomes as clinicians offer treatments both for catatonia itself as well as tailored treatments for its broad range of associated conditions.